IMPLEMENTASI PERLINDUNGAN HUKUM TENAGAKERJA OUTSOURCING YANG DITEMPATKAN PADA TOKO INDOMARET DIKELURAHAN DELIMA PEKANBARU - Delfi Aris Wanto; Hayatul Ismi; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Outsourcing workforce protection that is placed in the Indomaret store in Kelurahan Delima Pekanbaru needs to be done, this is because there are still many employers or companies who consider that workers are lowly slaves who can be treated at will. As a result of the employer's treatment, of course, many workers' rights as a human being are broken, the employer should treat the workers in a human condition and must follow the rules of the applicable laws.The issues discussed are first, concerning the employment agreement made between employers and workers based on Law No. 13 of 2003 on Manpower, and Second what form of legal protection provided by employers for workers under Law No. 13 of 2003 on Employment. The research method used is empirical research, another term used is Sociological legal research is also called field research and this research is descriptive. In data collection, the type of data used in this study are primary data and secondary data, namely directly through respondents (field), Law No. 13 of 2003 on Employment, Civil Code, legal journals and books related to research. This data analysis is done qualitatively and deductively deduced.From the results of research conducted by the author, found that maih there are rights of workers who are violated by employers or companies, so that workers are not directly harmed. Therefore, based on this law protection is required for outsourced workers working in Indomaret stores from the government.Keywords: Outsourced workers, Legal protection, Worker and Employee Rights